RANCANG BANGUN TRACKER PEMBANGKIT LISTRIK TENAGA SURYA MENGGUNAKAN EMPAT TITIK BERBASIS MIKROKONTROLER - Amalia, Syafira; Aryza, Solly; Tarigan, Amani D; Anisah, Siti; Hamdani, Hamdani (Scenario (Seminar of Social Sciences Engineering and Humaniora), 2021)
Solar cell is a device that converts radiation from sunlight into electrical energy directly, which is also called photovoltaic. Solar Module (Photovoltaic), functions to convert solar energy into DC electric current which is forwarded to the BCU (Battery Control Unit) device to be stored in the battery. Solar panel tracking is a solar panel tracking mechanism to produce perfect sunlight by being able to track and follow the direction of the sun so that the solar cell is always perpendicular to the sun so that the sun's use value received by the solar cell is more optimal. Each square meter of the surface area of the solar panels facing the sun directly by regulating the movement of the motor, the solar panels can absorb about 1000 W of energy from the sun (with an estimated useful power of up to 100.The solar energy capacity in Indonesia is very large, around 4.8 KWh / m2 or even the equivalent of 112,000 GWp, but only 10 MWp has been utilized and utilized